Penerapan Metode Extreme Programming Sistem Kearsipan Dokumen Berbasis Web - Arief Hidayatullah; Dianni Yusuf; Indira Nuansa Ratri (STMIK Budi Darma, 2024)
PT. Trisakti Pilar Persada, a consulting firm specializing in public policy, faces challenges in managing both physical and digital document archives. Currently, physical documents are stored on shelves, while digital ones are on a single computer. To address this, a web-based archiving system is proposed to aid admin in managing internal document layout and employee access. The system aims to enhance transparency by allowing public access to performance reports. Developed using Extreme Programming, it utilizes PHP with Laravel framework and MySQL database. Black-box testing ensures user satisfaction. Users include admins and the public, with features like user management, meeting archives, reports, contracts, and more. Testing results indicate high ratings across functionality of 87%, usability of 91,2%, efficiency of 87,3%, maintainability of 88%, and portability of 87%